Utilization of Styrofoam-Matrix for Coarse Aggregate to Produce Lightweight Concrete - Noor Asnan, Muhammad; Noor, Rusandi; Azzahra, Rafidah (International Journal of Engineering and Technology, 2019)
A lightweight coarse aggregate called Styrofoam-Matrix Aggregate (StyM) was developed to use in Lightweight Aggregate Concrete Compositions. This paper aims to present the characteristics of the developed StyM aggregrate to replace natural coarse aggregates in lightweight concrete mixtures. The presented characteristics are the compressive strength and the collapse pattern obtained experimentally. The experiment used styrofoam formed into balls with diameters of 25 to 35 mm coated with matrix as the core materials in StyM. The measurements of the characteristics were conducted after 14 days completed mixture of StyM 10% as a controlled volume, and StyM 100% replacement for coarse aggregate. The testing was conducted to observe the concrete compressive strength and the corresponding collapse patterns. For the hard concrete StyM 10% with the density of 2183 kg/m3, the compressive strength is 19.86 MPa, while for StyM 100% with the density of 1650 kg/m3, which is considered as lightweigh concrete, the compressive strength is 12.02 MPa. The collapse pattern shows in the form of columnar. This paper found that the developed Styrofoam coated matrix (StyM) aggregate can form lightweight aggregate concrete mixtures with superior mechanical and durability properties.Â Â